Changes on cylindrospermopsin concentration and characterization of decomposition products in fish muscle (Oreochromis niloticus) by boiling and steaming. (July 2017) - Guzmán-Guillén, Remedios; Maisanaba, Sara; Prieto Ortega, Ana I.; Valderrama-Fernández, Rocío; Jos, Ángeles; Cameán, Ana M.
Abstract: The occurrence of cylindrospermopsin (CYN) in toxic blooms of cyanobacteria is increasing in both frequency and distribution over the world. CYN persistence in water potentiates its accumulation in a wide range of aquatic animals destined to human consumption representing a serious problem. The aim of this work was to study for the first time the influence of cooking (boiling and steaming) for 1 or 2 min, on the stability of CYN in muscle of fish ( Oreochromis niloticus ) contaminated under laboratory conditions, also analyzing the waters in which samples were cooked. CYN was extracted and quantification was carried out by a developed and validated UPLC-MS/MS method. The results show that concentrations of CYN in fish are dependent on the cooking method, being the steaming for 2 min the most effective in reducing CYN levels (26%), followed by boiling for 2 min (18%), and significant differences have been found between the two periods assayed (1 min vs. 2 min). CYN was also detected in waters in which fish muscles were cooked in the range 0.10–0.28 μg/L. Moreover, characteristic decomposition products depending on the type of cooking were detected for the first time among the results of these treatments. The present findings emphasize the need for further studies to evaluate the influence of cooking in the presence of CYN in fish for a more realistic risk evaluation for the human health. Highlights: Boiling and steaming reduce CYN levels in cooked fish muscle. Higher reductions in CYN levels are obtained in steamed fish for 2 min. Cooking for 2 min is more effective in reducing CYN levels than cooking for 1 min. CYN was also detected in waters in which fish muscles were cooked. CYN decomposition products are detected in all samples after cooking.